The birds of Tinjil and Deli Islands, West Java - Derek A Holmes; Bas van Balen (Indonesian Ornithologists’ Union, 1996)
Pulau Tinjil and Pulau Deli are islands of 600 ha and 950 ha respectively lying 14 km off the south coast of West Java. The authors made six visits to one or other of the islands between 1988 and 1995. Both are covered with primary forest, but a large population of Long-tailed Macaque monkeys has recently been introduced on both islands as a free-range monkey-breeding facility. The islands have an depauperate avifauna with probably just 20 resident landbird species, common to both islands. These include one near-threatened species, the Nicobar Pigeon, which was formerly very common but which may have suffered as a result of the introduction of monkeys. Other small island/coastal specialists include the Beach Thick-knee, Pied Imperial Pigeon and Chestnut-capped Thrush. Except along the beaches, there are few forest-edge habitats, and most of the landbirds, including those normally occupying open habitats on the mainland such as White-breasted Waterhen, Yellow-vented Bulbul and Brown-throated Sunbird, have expanded their range to occupy the forest niche